RESEARCH OF FUNCTIONAL PARAMETERS OF INFOCOMMUNICATION NETWORKS 6G - VASYLKIVSKYI, Mykola; KOLOMIETS, Alyona; HRABCHAK, Nazarii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The work presents the results of research into 6G technology, which will allow integrating all types of access in one mobile phone, ensuring smooth switching between services. New options for the use of mobile networks, such as sensing and artificial intelligence, are considered, which form new indicators of the quality of the information service - the resolution of sensing and the probability of output. For new applications, the prospects for further research into related indicators, such as flexibility and scalability to support own artificial intelligence services and network reliability level, are considered. Prospects for the development of electronic health care based on mobile communication systems with increased requirements for reliability, availability, security and confidentiality are considered. A platform for aerial mobility of various high-resolution sensors and cameras for various industries based on unmanned aerial vehicles has been investigated. The fundamental energy limitations of calculations related to information processing, which are an important step on the way to the successful deployment of 6G wireless networks, are considered.In the design of next-generation wireless communication networks, it has been determined that traditional AI optimization algorithms (such as federated learning) usually consider the bandwidth or delay of wireless connections as a weight for distributed multiprocessor data exchange, without considering the power energy bounds between different devices in different regions. This ambiguous consideration of AI energy limitations or power costs may lead to a large divergence between the design of a wireless network and the actual deployment of AI in the future. For this reason, equal importance must be attached to green AI and green communications. Therefore, when designing the architecture of the 6G information communication system, it is necessary to fully consider the impact of artificial intelligence models, algorithms and equipment on energy consumption to provide economic benefits to customers with corresponding operating costs of the system.The peculiarities of providing users with access to Internet services at any time through the same device regardless of their location, which is one of the ultimate goals of creating effective wireless networks, are discussed. The proposed concept of green AI called Oncefor-All (once and forever), according to which it is proposed to train an information communication network with further specialization during deployment will allow for efficient logical implementation on many devices, taking into account the given resource constraints. At the same time, terrestrial and non-terrestrial 6G networks will be fully integrated at the system level, ensuring the convergence of services, radio interfaces, networks and user devices. By organically combining these two access environments into one converged multi-layer heterogeneous network covering the entire globe, 6G technology will provide users with the same service. Ensuring the global delivery of mobile services will be an important aspect of the development of the 6G network.
Keywords: information communication system; 6G technology; artificial intelligence; unmanned aerial vehicle; key performance indicator; wireless network